OC-k3 cells, an in vitro model for cochlear implant biocompatibility. (2nd October 2015) - Astolfi, Laura; Simoni, Edi; Martini, Alessandro
Abstract : Objective: In patients with severe or deep hypoacousis, the cochlear implant represents the only way to recover the ability to hear. Nevertheless, the insertion of a silicone-embedded electrode in the cochlea may produce damage through pressure, shock, bleeding and tissue perforation, which could cause apoptosis and necrosis in the organ of Corti. Another variable is the use of different silicone materials. Although all embedding silicone compounds are medical grade biocompatible, their effects in the inner ear environment have never been tested. Our aim was to assess whether polydimethylsiloxane (PDMS) compounds employed in cochlear implants could be cytotoxic to inner ear cells, by exposing an in vitro organ of Corti cell line (OC-k3) to four PMDS compounds (three fluid and one elastomere) and verifying whether or not any one of these compounds could lead to cell death by apoptosis or necrosis. Study design: To obtain a toxicity curve, OC-k3 cells were exposed to PDMS compounds (octadimethylsiloxane, hexadimethylsiloxane, decamethylcyclopentasiloxane and a silicon rod) at different dilutions and time of exposure, testing vitality by flux cytofluorometry and fluorescence microscopy. Investigations were extended to molecular interactions between OC-k3 cells and PDMS, testing cell death markers by immunocytochemistry and real-time PCR. Results: Among the fluid PDMS compounds, decamethylcyclopentasiloxane induced the highest significant cell mortality (at 1:100 dilution) after 48 h of treatment, followed by octadimethylsiloxane (1:10) and hexadimethylsiloxane (1:5) at 24 h. The silicon rod did not show any inner ear cell toxicity. Conclusion: In our experimental conditions, the observed cell mortality was not caused by release of cytotoxic molecules by PDMS on OC-k3 cells, but by the formation by PMDS of a surface film preventing air exchange. From a biomolecular point of view, PDMS compounds appear suitable for electrode coating in cochlear implants.